(untitled) (European Journal of Interdisciplinary Research and Development, 2025)
This article examines the organizational and economic challenges encountered in the development of small businesses within the service sector and explores possible solutions to these issues. In particular, it analyzes the opportunities and privileges provided by free economic zones for small business entities and their role in enhancing investment attractiveness. The service sector plays a crucial role not only in improving the quality of life of the population but also in increasing employment, fostering a competitive environment, and promoting innovative activities. Therefore, free economic zones are regarded as one of the key mechanisms for supporting small businesses and modernizing the service sector within the framework of the country’s long-term economic development strategy.